Aircraft Gust Alleviation Preview Control with a Discrete-Time LPV Model in Consideration of the Elastic Mode. Issue 28 (2019) - Uchida, Daisuke; Shimomura, Takashi; Hamada, Yoshiro
Abstract: This paper deals with a gust alleviation (GA) control system using gain-scheduled (GS) discrete-time preview control. A linear parameter-varying (LPV) model of an aircraft including a single elastic mode is developed. In order to effectively attenuate the vertical acceleration of a flexible aircraft in turbulence, we propose a two-input control system, in which the aileron in addition to the elevator is used as a control surface. It is shown that when turbulence is acting on the aircraft, the vertical acceleration of the aircraft is effectively reduced with the proposed control system through some numerical simulations.